2023
DOI: 10.1186/s40942-022-00439-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical classification for large macular hole: based on different surgical techniques results: the CLOSE study group

Abstract: Background The CLOSE study group proposes an updated surgical classification for large macular holes based on a systematic review of new treatments. Recently, many new techniques have been introduced to treat large full-thickness macular holes (FTMH); although the indications are not clear. An updated surgical classification is needed to help surgical decision-making. Methods We gathered published series by the CLOSE Study Group members and from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…In this research, the ROC curve analysis indicated that MLD was a robust predictive factor for the presence of A-type glial proliferation at 1 month, with a cut-off >547.5 μm, which suggested that patients with a MH >547.5 μm are quite possible to have a poor anatomical and visual prognosis after surgery. This result was similar to the previous studies suggesting a MLD of around 550 μm as a threshold of successful MH closure [19, 20]. Hypothetically, in large MHs (>547.5 μm), it is challenging for outer retinal layers to reapproximate so that a large amount of glial cells are required to fill the foveal defect.…”
Section: Discussionsupporting
confidence: 91%
“…In this research, the ROC curve analysis indicated that MLD was a robust predictive factor for the presence of A-type glial proliferation at 1 month, with a cut-off >547.5 μm, which suggested that patients with a MH >547.5 μm are quite possible to have a poor anatomical and visual prognosis after surgery. This result was similar to the previous studies suggesting a MLD of around 550 μm as a threshold of successful MH closure [19, 20]. Hypothetically, in large MHs (>547.5 μm), it is challenging for outer retinal layers to reapproximate so that a large amount of glial cells are required to fill the foveal defect.…”
Section: Discussionsupporting
confidence: 91%
“…Data from the "CLOSE" study group presents a practically 100% success rate of PPV with the use of ILM peeling and/or the creation of an ILM flap in the case of type S and M macular holes, while in the case of type L holes the success rate is reduced to 97%, for type XL holes 86% and for type XXL holes to 80% [4]. In our co- hort the total success rate of primary closure of macular hole was 93%, in which in the case of holes with preoperative MLD of ≤ 550 we achieved a 100% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort the success rate for type XL holes was only 46.7%, which raises the question as to whether it would be more advantageous to choose the technique of an ILM flap as the method of first choice for such holes. Although the authors of the "CLOSE" study group in 2023 demonstrated that there is a higher success rate of closure upon the use of a flap from the ILM for holes of types L, XL and XXL, the gains of BCVA are lower in comparison with gains of BCVA upon the use of ILM peeling only [4,11]. The lower gains of BCVA are probably due to the fact that manipulation of the flap from the ILM presents a higher risk of mechanical damage to the RPE, while the flap itself may lead to an excessive glial reaction and hyperproliferation of the Müller cells, which subsequently prevents the adequate reconstruction of the outer layers of the retina [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ILM peeling, no correlation was observed between the macular hole size and failure rate. 33,34 Further studies are required to determine whether the ERM should be completely removed or inverted together with the ILM flap.…”
Section: Discussionmentioning
confidence: 99%